Biomedical engineering principles - Ritter, Arthur B. (CRC Press, 2011)
Linking methodologies in engineering, medicine, biology, and physics, this reference clearly defines basic principles in image processing and biomechanics, the modeling of physiological processes, and bioelectric signal analysis for a solid understanding of devices and designs for improved functioning of the human body-including cutting-edge discussions of tissue engineering applications such as skin equivalents, cardiovascular components, bone regrowth, muscle tissue, and the regeneration of nerves. The author also discusses technologies at the forefront of cardiac care including total artificial hearts, left ventricular assist devices, defibrillators, pacemakers, and stents, as well as issues related to minimally invasive and robotic surgery, next-generation imaging devices, nanomotors, and nanodevices"--Provided by publisher.